CGRP neuropeptide levels in patients with endometriosis-related pain treated with dienogest: a comparative study - Shahla Chaichian; Ziba Dehghan Firoozabadi; Samaneh Rokhgireh; Kobra Tahermanesh; Abolfazl Mehdizadeh Kashi; Azam Govahi; Sara Minaeian; Mehdi Mehdizadeh; Marziyeh Ajdary (BMC, 2024)
Abstract Background and objective Endometriosis (EM) involves the peripheral nervous system and causes chronic pain. Sensory nerves innervating endometriotic lesions contribute to chronic pain and influence the growth phenotype by releasing neurotrophic factors and interacting with nearby immune cells. Calcitonin gene-related peptide (CGRP), a pain-signaling neurotransmitter, has a significant role. This study examines the effect of Dienogest (DNG), a hormone therapy used for managing EM -related pain, on serum CGRP levels in EM patients. Materials and methods The Visual Analog Scale (VAS) assessed pain in diagnosed EM. individuals. Serum samples were obtained to measure CGRP concentration. Participants received a 2 mg/day oral dose of DNG for six months as prescribed treatment. Additional serum samples were collected after this period to measure CGRP levels. Results In the EM group, 6.7%, 33.3%, and 20% had ovarian EM, ovarian plus uterosacral, and ovarian plus bladder, respectively. The EM group showed higher CGRP serum levels than the control group (80.53 ± 16.13 vs. 58.55 ± 6.93, P < 0.0001). Still, after drug administration, CGRP serum levels significantly decreased compared to pre-treatment levels (69.66 ± 11.53 vs. 80.53 ± 16.13, P < 0.05). The EM group showed higher pain compared to the control group (7.93 ± 1.58 vs. 0.13 ± 0.35, P < 0.0001), but after drug administration, pain significantly decreased compared to pre-treatment levels (1.00 ± 2.00 vs. 7.93 ± 1.58, P < 0.05). Conclusion DNG administration reduces pain and serum CGRP levels in EM patients, offering the potential for innovative treatments and tailored options. Understanding neurotransmitter roles and drug effects can aid in discovering more effective modulators for these pathways.